A Straightforward Method for Preparing Well‐Defined Responsive Diselenide‐Containing Polymers Based on ATRP. Issue 10 (30th March 2015) - Fan, Caiwei; Ding, Chunlai; Pan, Xiangqiang; Zhang, Zhengbiao; Zhu, Jian; Zhu, Xiulin
<x xml:space="preserve">Abstract</x> Diselenide‐containing polymers are facilely synthesized from polymers prepared by atom transfer radical polymerization (ATRP). Benefiting from the ATRP technology, this protocol provides a flexible route for controlling the polymer structure, which allows for a great variety of architectures of selenium‐containing polymer materials for applications in various fields. The oxidative and reductive responsive behavior of the obtained diselenide‐containing polymers is also investigated.